Designing Animated Pedagogical Agent (APA) to scaffold student learning in Online Problem-Based Learning Environment - Shahbodin, F. (2009)
Abstract—This paper describes on the idea in integrating animated pedagogical agent (APA) as an alternative approach as scaffolding in Problem-Based Learning (PBL). APA will be operated as a virtual tutor and guided learners through the learning process in PBL. It is suggested to provide the potential solution to replace the human tutor request in PBL